Usefulness of plasma full‑length glypican‑3 as a predictive marker of hepatocellular carcinoma recurrence after radial surgery - Miura, Masahiro; Fujinami, Norihiro; Shimizu, Yasuhiro; Mizuno, Shoichi; Saito, Keigo; Suzuki, Toshihiro; Konishi, Masaru; Takahashi, Shinichiro; Gotohda, Naoto; Suto, Kouzou; Yoshida, Tomokazu; Nakatsura, Tetsuya (Oncology letters, 2020)
Predicting the risk of hepatocellular carcinoma (HCC) recurrence before treatment is necessary for developing subsequent treatment policies. Several tumor markers found in blood, such as alpha-fetoprotein (AFP) and protein induced by vitamin K absence or antagonist-II (PIVKA-II), are presently used to determine the occurrence and recurrence of HCC and to predict patient prognosis. However, these markers are insufficient for these purposes as certain patients have HCC recurrence despite exhibiting negative AFP and PIVKA-II. The present study identified glypican-3 (GPC3), an embryonal carcinoma antigen that is expressed specifically in HCC and is secreted into blood. Although the N-terminal domain of GPC3 in sera may be a potential prognostic factor for HCC, its biological role remains unclear. By contrast, full-length GPC3 (FL-GPC3) is reported to serve important roles in cell differentiation, proliferation and signaling events that cause HCC. Given the biological roles of FL-GPC3 in HCC progression, the present study evaluated its potential as a predictive marker of HCC recurrence. In the present study, a novel measurement system was constructed to specifically measure plasma FL-GPC3. Subsequently, its ability to predict recurrence after radical surgery in 39 HCC patients was evaluated. The results revealed that preoperative FL-GPC3 levels in patients with recurrence were significantly higher than those in patients without recurrence, suggesting that FL-GPC3 could be a better predictive maker of risk of recurrence than AFP or PIVKA-II. Furthermore, it was determined that the combination of FL-GPC3, AFP and PIVKA-II could predict recurrence within one year of radical surgery with high sensitivity and specificity. Based on these results, the validation of FL-GPC3 as a predictive marker of HCC recurrence in a larger population is warranted.